Myopia in investment: Seasoned manager’s age and long-term investment distortion - Muhammad Madyan; Bayu Indra Kurniawan; Novian Abdi Firdausi (Jurnal Keuangan dan Perbankan, 2019)
Myopia in financial terms is included in the discussion of short-termism in investments. This study analyzes the effect of managerial age on investment policies taken by the top-level management with controlled variables consists of investment opportunity, firm size, profitability, leverage, and firm year effect. This study uses a fixed effect model estimation with data samples containing secondary data from 52 manufacturing firms listed in BEI. Data samples are selected through a purposive sampling method to filter and choose data that fit the study criteria. Study results show that the seasoned manager’s age has a negative and significant effect on long term investment, which implies that the older the seasoned manager’s age could increase the tendency of investment myopia. Controlled variables such as investment opportunity and firm size have a positive effect on long term investment, while the firm-year effect factor of 2013 and 2014 have positive effects but insignificant effect on long term investment.JEL Classification: D29, G32, G39, G41DOI: https://doi.org/10.26905/jkdp.v23i4.3393